2020
DOI: 10.29333/iji.2020.13248a
|View full text |Cite
|
Sign up to set email alerts
|

Work-integrated Learning Competencies: A Case Study in a Food Engineering Practice School Program

Abstract: There is increasing pressure on higher education to include work-integrated learning (WiL) in its programs in order to prepare graduates for the workplace. However, there is a lack of detailed competencies required for this type of learning. The purpose of this study was to identify competencies needed for workintegrated learning (WiL). The case study took place in a food engineering practice school program in a Thai university. It involved multiple quantitative and qualitative data-collection techniques over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In a WIL setting, [35], contend that communication can orange from arm's length where there's inadequate communication between the college and the firm to insert characterized by tall levels of communication. Furthermore, Kirtikara [36] found that dialect was a profoundly petulant issue in WIL Communications between firms and colleges as phrasing was befuddling and there was a small shared understanding.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a WIL setting, [35], contend that communication can orange from arm's length where there's inadequate communication between the college and the firm to insert characterized by tall levels of communication. Furthermore, Kirtikara [36] found that dialect was a profoundly petulant issue in WIL Communications between firms and colleges as phrasing was befuddling and there was a small shared understanding.…”
Section: Literature Reviewmentioning
confidence: 99%